Non-length dependent small fibre neuropathy/ganglionopathy. Issue 2 (2nd October 2007) - Gorson, K C; Herrmann, D N; Thiagarajan, R; Brannagan, T H; Chin, R L; Kinsella, L J; Ropper, A H
Abstract : Objective: To describe the clinical and laboratory features of a painful non-length dependent, small fibre ganglionopathy (SFG). Background: The syndrome of generalised SFG with early involvement of the face, trunk or proximal limbs is not well recognised and contrasts with the burning feet syndrome of small fibre neuropathy (SFN) and classical large fibre features of sensory ganglionopathy. Methods: Retrospective case review including skin biopsies from four neuromuscular centres. Patients with pre-existing diseases associated with ganglionopathies were excluded. Results: 12 men and 11 women, with an average age of 50 years, were studied. Neuropathic pain developed over days in eight and over months in the other patients. The face (n = 12), scalp (n = 10), tongue (n = 6), trunk (n = 15) and acral extremities (n = 21) were involved. Symptoms began in the hands or face before the legs in 10. The pain was characterised as burning (n = 22), prickling (n = 13), shooting (n = 13) or allodynic (n = 11). There was loss of pinprick sensation in affected regions in 19, with minimal or no loss of large fibre sensibility. Laboratory findings included abnormal glucose metabolism in six patients, Sjögren syndrome in three and monoclonal gammopathy, sprue and hepatitis C infection in one each, with the remainder idiopathic. Sensory nerve action potentials were normal in 12 and were reduced in the hands but normal in the legs in six. Skin biopsy in 14 of 17 showed reduced nerve fibre density in the thigh equal to or more prominent than in the calf. Two of seven patients improved with immune therapies, 13 symptomatically with analgesic medications and the remainder had little improvement. Ten considered the pain disabling at the last follow-up (mean 2 years). Conclusion: The pattern of symmetric, non-length dependent neuropathic pain with face and trunk involvement suggests a selective disorder of the dorsal ganglia cells subserving small nerve fibres. It can be distinguished from distal SFN. A potential metabolic or immune process was detected in half of the cases and the disorder was often refractory to treatment.